Kegiatan preservasi koleksi di Perpustakaan Institut Teknologi Nasional - Raisya Gita Cahyani; Ute Lies Siti Khadijah (Jurnal Informatio, 2023)
The Library of the National Institute of Technology (Itenas) has many collection of organic materials. The collection in this library is vulnerable to collection mild damage to severe levels so that preservation activities are one way to overcome them. The purpose of this research to find out preservation activity collection at The Library of the National Institute of Technology through preventive, curative, and restorative. The research method used qualitative descriptive. The results showed that biota like termite, and human factors like vandalism were the causes of the damage to the library collections. Librarian have been done preservation activity to minimize collection damage through preventive, curative, and restorative. Preventive preservation activity carried out through educational programs for library staff, provision and arrangement of collection storage areas, environmental control programs and implementation of security systems using CCTV. Curative preservation activity carried out through library cleaning as a periodically, it’s name Jumat Bersih (Clean Friday) Program, and fumigation activities. Restorative preservation activity carried out through binding and mending of damaged library collections. The preservation activities at The Library of National Institute of Technology has some constrains including lack of budget, facilities, and the small number of librarian who worked in preservation activities. Conclusion this research is librarian at The Library of National Institute of Technology has conducted preservation activities with proper procedure consist of preventive, curative, and restorative activities.